PENERAPAN METODE PRAKTEK DALAM PEMBELAJARAN WUDHU DAN SHALAT PADA MATA PELAJARAN FIKIH DI MIS KESUMA LKMD KECAMATAN NAMORAMBE KABUPATEN DELI SERDANG - Abdillah Idris; Ahmad Ridwan; Fathul Jannah (STKIP Subang, 2026)
This research is motivated by the problem of Fiqh learning that remains predominantly theoretical and lacks a practice-based approach, resulting in many students experiencing difficulties in performing wudu and prayer correctly in accordance with Islamic law. This study aims to describe: (1) the implementation of wudu and prayer learning in the Fiqh subject at MIS Kesuma LKMD, Namorambe District; (2) the application of the practice method in learning wudu and prayer; and (3) the supporting and inhibiting factors in the implementation of the practice method. This research employed a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation. Data validity was verified using source triangulation and technique triangulation. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the application of the practice method in learning wudu and prayer has a positive impact on students' understanding and skills. Through direct guidance from the teacher, students are able to repeatedly practice the acts of worship, thereby strengthening their memorization of the correct procedures, boosting their confidence, and forming proper worship habits in daily life. This method also proves more effective than the lecture method, as it engages students' cognitive, affective, and psychomotor aspects in an integrated manner.